Experimental methodology for bubble content measurement of thin films. (January 2021) - Zhang, Yibei; Zhao, Bing; Hu, Jianhui; Chen, Wujun; Deng, Xiaowei; Yu, Zhengyue; Xie, Chao; Peng, Fujun; Huang, Xiaofei
Abstract: The inclusion of micro bubbles often exists in polyimide films (PI) during the liquid molding process, which can largely affect the mechanical performance. However, there lacks an effective method to quantify the bubble content. Herein, an obvious tension variation of a pre-stressed polyimide film is observed firstly in a vacuum test. This phenomenon is assumed that, when the vacuum level of the testing environment increases, the inner bubbles would expand mainly out of plane, resulting in an in-plane contraction, and the tension varies accordingly. This tension variation ability is found quite stable despite of the stochastic micro-bubble distribution, which could be utilized to quantify the bubble content. Moreover, a film with meso-size bubbles is tested to have the similar tension variation ability. According to the experimental results, the tension variation ability can be basically stable when the bubbles in the length and width directions reach a certain number (e.g. 10). Highlights: A tension variation of films containing bubbles is observed when the vacuum level of the testing environment increases. The tension variation ability is verified stable despite the stochastic distribution of the micro bubbles in films. A film with meso-size bubbles has been tested to exhibit the same tension variation ability. The bubble distribution in films can be assumed as uniform when the amount of meso-size bubbles reaches a certain number. The proposed methodology is proved effective to determine the bubble existence and quantify the bubble content of thin films.